A new genus and new species of Phlaeobinae from China (Orthoptera: Acrididae) - Yin, Xiang-Chu; Yin, Hong (Zootaxa, 2007)
This paper reports a new genus of Phlaeobinae i.e. Sinophlaeobida gen. nov and a new species Sinophlaeobida taiwanensis sp. nov. The new genus is similar to Phlaeobida I. Bolivar, 1902, but differs from the latter in: 1) lateral carinae of pronotum nearly parallel. 2) prozona about 1.6 times longer than metazoan and 3) hind margin of pronotum incised slightly in the middle.